Theoretical Aspects Of Ecological Intelligence Development Of Students In Elementary Schools - Zulfikar, Hari Ahmad; Supriatna, Nana; Nurbaeti, Iyus (International Conference on Elementary Education, 2020)
The environment is defined as a place where living things carry out their life activities. Clean and sustainable environment can sustain continuous life(sustainability).Therefore, intelligence is needed to support it, one of the intelligence that is the basis for this ecological intelligence (ecoliteracy). Every behavior or action of a person based on ecological intelligence,it does not only have an impact on himself and others, but also on other living things and the nature around where a person lives or in other terms "empathy for all forms of life". Current conditions in elementary schools have not shown students who have ecological intelligence. The development of social skills or character of students in elementary schools still focuses on human interaction. Through ecopedagogy, teachers need to link interactions between humans and the environment or nature. The purpose of writing this article is to describe some aspects of the theory of ecological intelligence development of students in elementary schools. This study uses a literature study (literature review) which produces a description of several theories in developing ecological intelligence of students in elementary schools